Benzofuroxan derivatives N-Br and N-I induce intrinsic apoptosis in melanoma cells by regulating AKT/BIM signaling and display anti metastatic activity in vivo. Issue 1 (December 2015) - Farias, C.; Massaoka, M.; Girola, N.; Azevedo, R.; Ferreira, A.; Jorge, S.; Tavares, L.; Figueiredo, C.; Travassos, L.
Abstract Background Malignant melanoma is an aggressive type of skin cancer, and despite recent advances in treatment, the survival rate of the metastatic form remains low. Nifuroxazide analogues are drugs based on the substitution of the nitrofuran group by benzofuroxan, in view of the pharmacophore similarity of the nitro group, improving bioavailability, with higher intrinsic activity and less toxicity. Benzofuroxan activity involves the intracellular production of free-radical species. In the present work, we evaluated the antitumor effects of different benzofuroxan derivatives in a murine melanoma model. Methods B16F10-Nex2 melanoma cells were used to investigate the antitumor effects of Benzofuroxan derivatives in vitro and in a syngeneic melanoma model in C57Bl/6 mice. Cytotoxicity, morphological changes and reactive oxygen species (ROS) were assessed by a diphenyltetrasolium reagent, optical and fluorescence microscopy, respectively. Annexin-V binding and mitochondrial integrity were analyzed by flow cytometry. Western blotting and colorimetry identified cell signaling proteins. Results Benzofuroxan N-Br and N-I derivatives were active against murine and human tumor cell lines, exerting significant protection against metastatic melanoma in a syngeneic model. N-Br and N-I induce apoptosis in melanoma cells, evidenced by specific morphological changes, DNA condensation and degradation, and phosphatidylserine translocation in the plasma membrane. The intrinsic mitochondrial pathway in B16F10-Nex2 cells is suggested owing to reduced outer membrane potential in mitochondria, followed by caspase −9, −3 activation and cleavage of PARP. The cytotoxicity of N-Br and N-I in B16F10-Nex2 cells is mediated by the generation of ROS, inhibited by pre-incubation of the cells with N-acetylcysteine (NAC). The induction of ROS by N-Br and N-I resulted in the inhibition of AKT activation, an important molecule related to tumor cell survival, followed by upregulation of BIM. Conclusion We conclude that N-Br and N-I are promising agents aiming at cancer treatment. They may be useful in melanoma therapy as inducers of intrinsic apoptosis and by exerting significant antitumor activity against metastatic melanoma, as presently shown in syngeneic mice.